Ethical Dilemmas in Deceased Organ Donation and Allocation – An Emerging Challenge in India. (July 2018) - Navin, Sumana; Suriyamoorthi, Sujatha; Shroff, Sunil
Abstract : Objectives: To analyze ethical dilemmas arising in India from deceased organ donation and allocation relating to WHO Guiding Principles 9 and 11. WHO Guiding Principle 9 (Distributive justice and equity) relating to organ donation and transplantation states that donated organs should be made available to patients based on medical need and not financial or other considerations. WHO Guiding Principle 11 states that the organization and execution of donation and transplantation activities, as well as their clinical results, must be transparent and open to scrutiny, while ensuring that the personal anonymity and privacy of donors and recipients are always protected. Methods: Three cases in India involving ethical dilemmas relating to WHO Guiding Principles 9 and 11 were studied. The first case involved breach of confidentiality of deceased donor and recipient in media reports. The media reported the recipient's name along with information that the recipient's family was in financial difficulty. Although the donor was not named, there was enough circumstantial detail that allowed the donor family to make the link between the donor and recipient. The donor's family then wanted to financially assist the recipient so as not to allow their donation to go "in vain". The second and third cases dealt with directed and conditional donation. The second case involved a request for directed but unconditional donation. The third case involved a conditional donation. This condition was rejected by the local authority and the case went on appeal to higher authorities. Results: The first case occurred in an ecosystem where the numbers of deceased donation are few. It highlights the difficulty in maintaining donor and recipient confidentiality even though the donor's name was not mentioned. In the second case the local authority allowed the directed donation to take place even though the recipient was not on the hospital's transplant waitlist. In the third case the family of the deceased agreed to donate only if an organ was given to the deceased's brother. The resolution of this case required the intervention of the national authority. Conclusions: The rising number of deceased donations will see an increasing incidence of ethical dilemmas regarding donation and allocation. Hospitals and media will need to balance publicizing success stories of organ transplants while maintaining donor and recipient confidentiality. Since clinical demand still outstrips organ donation rate, clearly defined allocation criteria are required. Criteria should accord with human rights and should not be based on a recipient's gender, race, religion, or economic condition. In certain situations, a multidisciplinary expert panel can mediate taking into consideration medical factors, community values, and general ethical rules.